Analisis Beban Kerja Mental Penjahit Menggunakan Metode NASA-TLX Pada CV. XYZ - Jastika Amelia Atmaja; Ferida Yuamita (CV. ALIM'SPUBLISHING, 2025)
CV. XYZ is a company that works in the service sector and produces sports gloves (golf, equestrian, etc.). From production data, the number of requests for gloves increased greatly in June-October, the number of requests was above 5000. Workers felt tired due to age, level of pattern difficulty, type of glove material and age of machines so that many employees experienced fatigue which resulted in a decrease in work productivity. The aim of this research is to find out how high or large the mental load faced by workers at CV. Cahaya Setia Mulia using the NASA-TLX method. In this research, the population is the tailors at CV. XYZ, totaling 16 people. Based on the research results obtained, of the 16 respondents there were 9 respondents in the very high category, 2 respondents in the high category, and 4 respondents in the somewhat high category. And of the 6 NASA-TLX indicators, the highest indicator is Physical Demands (PD) of 76.0 and the lowest is the Frustration (FR) indicator of 58.7. Proposed improvements include adding 5 tailors to the workforce of 5 tailors, 2 madome tailors, 1 zigzag tailor or increasing rest time to 1 hour and reducing working hours on Saturdays to 5 hours.